GAMBARAN ANALISIS HEMOGLOBIN PASIEN DENGAN DUGAAN TALASEMIA Β MAYOR YANG DIRAWAT INAP DI RSUP DR. M. DJAMIL PADANG - Azura, Rahla; Rofinda, Zelly Dia; Rusjdi, Selfi Renita; Husni, Husni; Mahata, Liganda Endo; Fadila, Zurayya (SINERGI : Jurnal Riset Ilmiah, 2025)
Background: Beta thalassemia major is a genetic blood disorder inherited by parents thalassemia traits (carrier) characterized by abnormal hemoglobin formation. Abnormalities during the process of hemoglobin formation cause gene changes or mutations that cause symptoms of severe anemia which has a long-term clinical impact on patients. High performance liquid chromatography can be used to determine the description of abnormal hemoglobin analysis, thus suspected diagnosis of thalassemia β major can be established by the clinician as a definitive diagnosis to enhance a more comprehensive diagnosis. Primary theraphy of beta thalassemia major is blood transfusion to support the quality of life regularly throughout the patient's life, transfusion of patients requires measurements such as pre-transfusion hemoglobin levels.  Objective: This study aims to determine the description of the results of the analysis of hemoglobin patients with suspected thalassemia beta major at RSUP Dr. M. Djamil Padang. Methods: This study used a cross sectional design.  The sampling technique uses total sampling with a total sample of 19 people from 1-35 years old. Patient data was from the suspected diagnosis of medical records established by clinicians at Dr. M. Djamil Hospital Padang. This data was analyzed univariately. Results: The results of this study indicated is mostly female with an average age of 13,74 years (SD ±12.1). This study resulted in a low pretransfusion hemoglobin average of 6.20 g/dL. The results of hemoglobin analysis for beta thalassemia major with average HbA (48,1%), HbA2 (27,3%) and HbF (24,5%). Conclusion: The results of the examination hemoglobin analysis on the HPLC method had results that did not compatible predictions of the suspected diagnosis of beta thalassemia major from the clinician